South Indian Carnatic singing and Irish Sean-nós - an ethnographic, musical and linguisticcomparison - Radhakrishnan, Mahesh (2016)
Despite sharing some interesting linguistic and possible cultural connections from a very distant past, South Indian and Irish musical cultures have emerged from highly distinct contexts and influences. Drawing on doctoral field research within the respective traditions as practiced in Australia as well as experience as a student and performer, this paper presents a comparison of Carnatic and Sean-nós singing from the perspectives of anthropology, ethnomusicology and linguistics and outlines some significant areas of connection and contrast. This analysis of two diasporic traditions in an antipodean settler context represents an innovative departure, by focusing not on the heartlands of these musical traditions, but on their existence in an urban, transnational context, dominated by an Anglo-Australian majority. Such a comparison reveals differing perspectives on both traditions.